2021
DOI: 10.1136/rmdopen-2021-001591
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin is unlikely to prevent rheumatoid arthritis in high risk individuals: results from the prematurely stopped STAtins to Prevent Rheumatoid Arthritis (STAPRA) trial

Abstract: ObjectivesPersons at high risk of rheumatoid arthritis (RA) might benefit from a low-risk pharmacological intervention aimed at primary prevention. Previous studies demonstrated disease-modifying effects of statins in patients with RA as well as an association between statin use and a decreased risk of RA development. A randomised, double-blind, placebo-controlled trial investigated whether atorvastatin could prevent arthritis development in high-risk individuals.MethodsArthralgia patients with anticitrullinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In agreement, previous studies reported the similar antioxidant potential for Sim in rat models of arthritis (Ahmed et al, 2015) and ischemic heart failure (Cho et al, 2014). Statins can inhibit oxidative stress by lowering the release of lipid peroxide MDA and NO (Fenster et al, 2003;van Boheemen et al, 2021). Elevation of MDA levels in the arthritic mice could trigger cell membrane damage of synovial membrane cells and increase free radicals production leading to oxidative stress damage particularly when endogenous antioxidant systems fail to compensate for the ROS.…”
Section: O N L I N E F I R S T a R T I C L Esupporting
confidence: 85%
“…In agreement, previous studies reported the similar antioxidant potential for Sim in rat models of arthritis (Ahmed et al, 2015) and ischemic heart failure (Cho et al, 2014). Statins can inhibit oxidative stress by lowering the release of lipid peroxide MDA and NO (Fenster et al, 2003;van Boheemen et al, 2021). Elevation of MDA levels in the arthritic mice could trigger cell membrane damage of synovial membrane cells and increase free radicals production leading to oxidative stress damage particularly when endogenous antioxidant systems fail to compensate for the ROS.…”
Section: O N L I N E F I R S T a R T I C L Esupporting
confidence: 85%
“…In particular, the hypothetical model presented in Figure 2 suggests that repeat evaluation for evolving autoantibody positivity at 1 year can be informative, and this may be a 'real life' clinical scenario and follow-up period. Furthermore, these findings may be applied going forward in clinical trial development for RA prevention to identify individuals who are at particularly high-risk for imminent onset of clinical IA/RAand indeed several existing clinical prevention trials have as inclusion criteria either high-positive ACPA levels, or positivity for ACPA plus combinations of RF isotypes (7)(8)(9). Importantly, many prospective studies of pre-RA have utilized individuals who have initially presented to healthcare with arthralgia and were subsequently found to have autoantibody positivity (14,16); while the Healthfair cohort studied herein still had a substantial portion of individuals with some joint symptoms at baseline and therefore may be somewhat comparable to individuals identified through clinics, ~30% of ACPA(+) individuals who later developed RA did not report joint pain at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrate that there is a period of seropositive rheumatoid arthritis (RA) development that can be termed 'Pre-RA' during which there are elevations of circulating autoantibodies including antibodies to citrullinated protein antigens (ACPA) and rheumatoid factor (RF) in absence of and prior to the appearance of clinically-apparent inflammatory arthritis (IA) as well as a clinical diagnosis of RA (clinical RA) that may further classifiable by established criteria (1)(2)(3). Importantly, these autoantibodies may play a pathogenic role in the development of RA (4,5); furthermore, the diagnostic accuracy of these autoantibodies for the future onset of clinical IA/RA has underpinned the development of several clinical prevention trials (1,(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Those at risk may face complex decisions around accepting predictive assessments and risks associated with immunomodulatory interventions in exchange for uncertain benefit. A recent trial of 40mg atorvastatin daily for three years to prevent arthritis development in seropositive arthralgia patients was terminated prematurely due to unwillingness to participate (33). A related qualitative study exploring barriers to trial participation highlighted perceptions that the need for treatment was low and outweighed by concerns about treatment risks and the burden of trial participation (34).…”
Section: Introductionmentioning
confidence: 99%